New nanofiber glaucoma drainage implant: Effectiveness, safety, first in vivo results, and optimization of surgical technique - Adela Klezlova; Petr Bulir; Alexandr Stepanov; Andrea Sidova; Magdalena Netukova; Jana Vranova; Katarina Urbaniova; Martina Grajciarova; Lenka Vankova; Zbynek Tonar; Pavel Studeny (PLoS ONE, 2025)
Purpose The purpose of the study is to evaluate the effectiveness, surgical preoperative and postoperative complications, histopathological findings, and optimize surgical technique after implantation of the new nanofiber glaucoma drainage implant (GDI). Method Implantation of the GDI, a unique nanofiber drainage device fabricated from polyvinylidene fluoride (PVDF) using the well-established electrospinning technology on the Nanospider™ platform, was first optimized in vitro on cadaver porcine bulbs before the initial in vivo implantations. PVDF was selected due to its favorable properties, including biocompatibility, anti-adhesive behavior, and mechanical stability, which are particularly advantageous in minimizing fibroblast colonization and fibrotic encapsulation. The Nanospider™ technology allows for reproducible, large-scale fabrication of nanofiber materials with controlled fiber morphology, which ensures uniformity and precision of implant dimensions. An in vivo study on 28 normotensive eyes from 14 laboratory New Zealand White rabbits was conducted. There were two groups of animals: the study group (14 eyes) and the control group (14 contralateral eyes). The study group underwent implantation of the new nanofiber GDI; the control group did not undergo any surgical procedure. Intraocular pressure (IOP) was measured preoperatively and at regular times postoperatively (Tono-Pen AVIA®). Preoperative and immediate postoperative complications were monitored. Histological quantification was performed using unbiased sampling and stereological methods to assess leukocyte infiltration, type I and type III collagen fractions, and both absolute and relative levels of inflammation. Results Based on the previous results and in vitro surgical experiences, the implant was narrowed to 2.0 mm, a thickness of 100 µm was chosen, and the implant was fixed with two scleral stitches to maintain its position. No serious preoperative complications occurred during in vivo experiments. There was one extrusion of the glaucoma implant noted after surgery, likely due to insufficient conjunctival fixation. This animal was excluded from both the study and the control groups. No serious instances of intraocular hypotension were observed after surgery. All animals tolerated the surgical procedure well, and the postoperative period was without any serious issues. In the study group, the average preoperative IOP was 13.6 mmHg (±4.1, n = 13). The average postoperative IOP on the first day, one, two, and three weeks, and one month after surgery decreased to 8.8 mmHg (±3.3, n = 13), 9.8 mmHg (±2.0, n = 13), 10.3 mmHg (±3.6, n = 13), 10.2 mmHg (±2.6, n = 13), and 9.7 mmHg (±2.0, n = 13), respectively. In the control group of contralateral eyes, the average preoperative IOP was 11.42 mmHg (±4.2, n = 13). The average postoperative IOP was 11.8 mmHg (±5.4, n = 13), 14.2 mmHg (±4.6, n = 13), 14.5 mmHg (±3.4, n = 13), 14.0 mmHg (±3.8, n = 13), and 14.2 mmHg (±2.4, n = 13), respectively, at the same follow-ups. In the study group, the IOP was statistically significantly lower by 29% at the end of the follow-up compared to the preoperative measurements ( p = 0.009). Eyes with the implant showed greater leukocyte infiltration and less type I collagen compared to the group without implants. The ratio of type I to type III collagen was lower in the implant group, indicating delayed maturation and weaker connective tissue during early healing. Conclusion For easier implantation, minor technical adjustments such as implant narrowing and scleral fixation of the GDI were developed and tested using in vitro experiments. In vivo implantation of unique nanofiber GDI appeared safe and technically well-suited for our study. No serious perioperative or postoperative complications were observed. There was one scleral extrusion of the device, which was, in our opinion, caused by insufficient conjunctival fixation. A statistically significant IOP reduction was achieved at the end of the follow-up in the study group with implanted GDIs. Further studies on the effectiveness of the implant with longer monitoring periods, together with other surgical options such as combined cataract surgery and nanofibers GDI, are needed.